Decreasing Incidence and Determinants of Bacterial Pneumonia in People With HIV: The Swiss HIV Cohort Study. (18th November 2021) - Balakrishna, Suraj; Wolfensberger, Aline; Kachalov, Viacheslav; Roth, Jan A; Kusejko, Katharina; Scherrer, Alexandra U; Furrer, Hansjakob; Hauser, Christoph; Calmy, Alexandra; Cavassini, Matthias; Schmid, Patrick; Bernasconi, Enos; et al.
Abstract: Background: Bacterial pneumonia is a leading reason for hospitalization among people with HIV (PWH); however, evidence regarding its drivers in the era of potent antiretroviral therapy is limited. Methods: We assessed risk factors for bacterial pneumonia in the Swiss HIV Cohort Study using marginal models. We further assessed the relationship between risk factors and changes in bacterial pneumonia incidence using mediation analysis. Results: We included 12927 PWH with follow-ups between 2008 and 2018. These patients had 985 bacterial pneumonia events during a follow-up of 100779 person-years. Bacterial pneumonia incidence significantly decreased from 13.2 cases/1000 person-years in 2008 to 6.8 cases/1000 person-years in 2018. Older age, lower education level, intravenous drug use, smoking, lower CD4-cell count, higher HIV load, and prior pneumonia were significantly associated with higher bacterial pneumonia incidence. Notably, CD4 cell counts 350–499 cells/μL were significantly associated with an increased risk compared to CD4 ≥ 500 cells/µL (adjusted hazard ratio, 1.39; 95% confidence interval, 1.01–1.89). Decreasing incidence over the last decade can be explained by increased CD4-cell counts and viral suppression and decreased smoking frequency. Conclusions: Improvements in cascade of care of HIV and decrease in smoking may have mediated a substantial decrease in bacterial pneumonia incidence. Abstract : Bacterial pneumonia in people with HIV is associated with obstructive airway disease, proton pump inhibitors, CD4 cell count, viral load, smoking, and intravenous drug use. Improved HIV care and decreased smoking may have mediated reduced bacterial pneumonia incidence 2008–2018.